When you get the diagnosis: ADHD primer for parents. Issue 10 (October 2015) - Knopf, Alison
<x xml:space="preserve">Abstract</x> When their children are diagnosed with a disease that has no cure, parents are concerned, even terrified. But there's no reason for panic. While their worries are understandable, there are many treatment options, and parents — by being the main advocate for their child — can make sure that all possible resources are used to the child's best advantage.